2009
DOI: 10.1002/chem.200900799
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Salan Aluminium Ethyl Complexes and Their Application in Lactide Polymerization

Abstract: Synthetic routes to aluminium ethyl complexes supported by chiral tetradentate phenoxyamine (salan-type) ligands [Al(OC(6)H(2)(R-6-R-4)CH(2))(2){CH(3)N(C(6)H(10))NCH(3)}-C(2)H(5)] (4, 7: R=H; 5, 8: R=Cl; 6, 9: R=CH(3)) are reported. Enantiomerically pure salan ligands 1-3 with (R,R) configurations at their cyclohexane rings afforded the complexes 4, 5, and 6 as mixtures of two diastereoisomers (a and b). Each diastereoisomer a was, as determined by X-ray analysis, monomeric with a five-coordinated aluminium ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(76 citation statements)
references
References 97 publications
2
73
0
1
Order By: Relevance
“…Although the stereoselectivity observed was not particularly high, the findings here are interesting because the change of selectivity was due to the variation of substituents on R 1 , R 3 , and R 4 in the similar initiator structures. Such a strategy of modulation of tacticity by changing substituents has been utilized in other aluminum 13 and zirconium 24 systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the stereoselectivity observed was not particularly high, the findings here are interesting because the change of selectivity was due to the variation of substituents on R 1 , R 3 , and R 4 in the similar initiator structures. Such a strategy of modulation of tacticity by changing substituents has been utilized in other aluminum 13 and zirconium 24 systems.…”
Section: Resultsmentioning
confidence: 99%
“…9 The pioneering works by Spassky 10 in the control of PLA microstructure showed that a chiral salen aluminum complex (Scheme 1; I , where R = ( R )-2,2′-binaphthyl, R 1 = R 2 = H, X = OMe) was highly isoselective for the ROP of rac -lactide. This system was further exploited 11 and expanded to other salen species, 12 their reduced derivatives such as salan ( II ; Scheme 1) 13 and salalen, 14 and related N 2 O 2 ( III ; Scheme 1) and N 4 type ligands. 15 These initiators typically feature a five-coordinate aluminum center supported by dianionic, tetradentate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The two chloro-substituted complexes, 43 and 44, gave the highest level of heterotacticity with P r = 0.96 and 0.88, respectively. Feijen developed a series of aluminum salan complexes with a cyclohexyl diamine bridge, with both racemic and (R,R) analogues (47). Racemic and enantiopure complexes with either no phenoxy substitution or methyl phenoxy substitution gave isotactic enriched PLA but with only moderate isoselectivity (P m up to 0.66), while chloro phenoxy substitution yielded heterotactic biased PLA (P r up to 0.73).…”
Section: Catalyst Tuningmentioning
confidence: 99%
“…Historically however, of the main group metals, aluminium complexes have played an important role in the development of copolymerization reactions of carbon dioxide and should be investigated further. Importantly, aluminium complexes are known to catalyse a wide range of other polymerization reactions including ring-opening polymerization (ROP) of cyclic esters [14][15][16][17][18][19][20][21][22][23][24][25][26] and trimethylene carbonate, 18,27,28 and cationic polymerization of alkenes (incl. isoprene, benzofuran and styrenes).…”
Section: Introductionmentioning
confidence: 99%